Factors Determining the Successful Performance of Baitul Maal Wat Tamwil in Wonosobo - Dawami, Qosdan; Razak, Dzuljastri Abdul; Hamdan, Hamdino (International Journal of Islamic Economics and Finance (IJIEF), 2021)
Notwithstanding Baitul Maal wat Tamwil (BMT) has spread tremendously over the past three decades in Indonesia, some of them faced various obstacles that hamper their effectiveness and sustainability. While some of others sustained and developed well, even in the economic crisis conditions. Hence, this study aims to investigate the factors that determine the successful performance of BMT. This study is a field research with triangulation as a mixed method approach through semi-structured interviews and questionnaires. Whereby the empirical data were collected by means of conducting semi-structured interviews with 3 managers of the BMTs and administering questionnaires to 285 employees of the BMTs. This study examined five factors that influence the BMT performance, namely the capital structure of funding, the governance of the BMT, the human resource adequacy, the product innovation and the repayment of financing products. The results pointed that among the five selected factors, only three factors had positive and significant influence on the successful performance of the BMT, they are the capital structure of funding, the human resource adequacy and the product innovation. The result of this study will also assist policy makers and the BMT managers in further improving the effectiveness and sustainability of the BMT in Indonesia.